High Number of Positive Rapid Plasma Reagin With Low Titers Using the Automated AIX 1000 RPR System. Issue 1 (11th January 2022) - Palavecino, Elizabeth L.; Soltani, Sohaila; Keller, Ryan; Elliott, Stephanie; McNeil, Candice J.
Abstract : The automated AIX1000 RPR test provides more reactive rapid plasma reagin results with low titers that are not confirmed by Treponema pallidum particle agglutination compared with manual rapid plasma reagin. Abstract: This study evaluated the performance of manual rapid plasma reagin (RPR) and automated AIX1000 RPR tests for the diagnosis of syphilis. Manual RPR showed a 3% reactive result compared with 5.8% for the automated test mainly because of RPR reactive results with low titers not confirmed by Treponema pallidum particle agglutination.